2017
DOI: 10.1001/jamaneurol.2017.2073
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Combining a Simulation-Based Method With a Lecture-Based Method for Fundoscopy Training in Neurology Residency

Abstract: IMPORTANCE Fundoscopic examination is an essential component of the neurologic examination. Competence in its performance is mandated as a required clinical skill for neurology residents by the American Council of Graduate Medical Education. Government and private insurance agencies require its performance and documentation for moderateand high-level neurologic evaluations. Traditionally, assessment and teaching of this key clinical examination technique have been difficult in neurology residency training.OBJE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 13 publications
0
16
0
1
Order By: Relevance
“…There are few devices in use, and currently only fundoscopy training as well as lumbar puncture training has been used for simulation-based methods training in neurology residency-each using commercially available (Kyoto Kagaku America Inc) simulators. [6][7][8][9] In neurocritical care, however, few so-called scenarios (a written script superficially resembling a screenplay) have been systematically tested. We and others have developed scenarios for the determination of brain death, which includes a combination of pitfalls and confounders.…”
Section: Introductionmentioning
confidence: 99%
“…There are few devices in use, and currently only fundoscopy training as well as lumbar puncture training has been used for simulation-based methods training in neurology residency-each using commercially available (Kyoto Kagaku America Inc) simulators. [6][7][8][9] In neurocritical care, however, few so-called scenarios (a written script superficially resembling a screenplay) have been systematically tested. We and others have developed scenarios for the determination of brain death, which includes a combination of pitfalls and confounders.…”
Section: Introductionmentioning
confidence: 99%
“…5 Over the last 10 years, neurology residencies have been utilizing simulation to enforce principles for managing acute stroke, 6 to train residents to perform lumbar punctures, 7 and to teach residents about direct ophthalmoscopy. 8 There is a dearth of literature suggesting use of a simulation center for developing professionalism and interpersonal communication skills, particularly in neurology residency. Nonetheless, simulation can positively affect physician performance and clinical outcomes, as has been demonstrated with screening for high-risk behaviors, 9 safer opioid prescribing practices, 10 and assessing pain.…”
Section: Discussionmentioning
confidence: 99%
“…Among neurological skills, an optic nerve sheath diameter trainer has been validated [59], while fundoscopic exam and lumbar puncture task trainers have both exhibited benefit [60,61]. A study comparing the lumbar puncture skills of simulation-trained internal medicine residents to traditionally trained neurology residents found that the simulation-trained residents showed superior performance despite significantly less clinical experience with the procedure.…”
Section: Task Trainersmentioning
confidence: 99%